Partial enrichment of phospholipids by enzymatic hydrolysis and membrane filtration of whey protein phospholipid concentrate - A.V. Swaminathan; M.S. Molitor; K.J. Burrington; D. Otter; J.A. Lucey (JDS Communications, 2023)
Whey protein phospholipid concentrate (WPPC) contains high amounts of phospholipids (PL; 4.5 ± 1%) but there is interest in further enriching the PL content for nutritional and functional applications. Chemical methods were unsuccessful in separating PL from proteins due to the presence of protein-fat aggregates. Instead, we explored hydrolysis of the proteins to peptides with the objective of removing peptides, thereby concentrating the PL fraction. We used microfiltration (MF) with a pore size of 0.1 µm to help reduce protein/peptide retention. Hydrolyzing proteins should facilitate passage of low molecular weight peptides through the MF membrane, while concentrating fat and PL in the MF retentate. Bench-top experiments were performed to select the proteolytic enzyme that resulted in the most extensive hydrolysis of proteins in WPPC from among 5 different commercial proteases. Sodium dodecyl sulfate-PAGE analysis was performed to measure the extent of protein hydrolysis over a period of 4 h. Alcalase enzyme was found to exhibit the highest proteolytic activity at conditions of pH 8 and temperature 55°C. The intensity of major protein bands (milkfat globule membrane proteins, caseins, β-lactoglobulin) in WPPC decreased in sodium dodecyl sulfate-PAGE profiles as hydrolysis progressed, along with the appearance of low molecular weight bands. Pilot-scale MF production, coupled with diafiltration (DF), of the hydrolyzed sample aided in the removal of peptides that caused an ~18% reduction in protein content with the final retentate having a total PL content of 9.3% dry basis (db) with protein and fat contents at approximately 43.8 ± 0.4% (db) and 48.9 ± 1.2% (db), respectively. The MF permeate had minimal fat content, indicating that there was no transmission of lipids or PL through the membrane during the MF/DF process. Confocal laser scanning microscopy and particle size analysis of enzyme hydrolyzed solution revealed that protein aggregates were still present after 1 h of hydrolysis. Complete removal of proteins and peptides was not achieved by this process, suggesting that a combination of enzymes would be needed for further hydrolysis of protein aggregates in WPPC solution to further enrich the PL content.